STRATEGI PENANGANAN AIR TERPRODUKSI DI INDUSTRI MINYAK DAN GAS DI LAPANGAN SPR LANGGAK MFK BLOK KABUPATEN ROKAN HULU - Vivi Rachmawati (Pelantar Press, 2023)
Oil and gas exploration, also known as hydrocarbon exploration, is a process that encompasses many different fields and requires learning about the geological conditions from geophysicists or other geoscientists as well as petroleum professionals in order to locate hydrocarbon reserves such as oil and gas. Mud, gas (H2S, CO2, and CO), and generated water are among the by products of oil and gas exploration. Produced water is one of the potential water resources that could be used by the community for daily needs due to the oil and gas industry's extensive production of it. However, at the moment, produced water is still viewed as industrial waste because it contains dangerous chemicals and other components that are found in oil and gas, which makes it potentially harmful to humans and can pollute the environment. Laboratory tests' findings demonstrate that the produced water samples' results have complied with the established standards for quality